Le zombie dans World War Z, métaphore d’une pandémie globale - Thomas Michaud (Caliban: French Journal of English Studies)
The novel World War Z describes an epidemic of zombies whose origin is in China and which decimates humanity in a few years. The zombic imagination allows us to wonder about the destabilization of human organizations in the face of a global pandemic. Collapsological theories envisage the end of technostructure by phenomena like epidemics. It is a form of neoapocalyptic thought reflecting the doubts of American and Western civilization following attacks such as 9/11. The reintoduction of zombies by the entertainment industry makes it possible to reactivate ancestral fears and crystallize the most violent anxieties and aspirations of society. The mythology of zombies serves as a sectorial myth for medicine, and more particularly for actors responsible for the regulation of epidemics that can potentially decimate humanity.